The comparison of different BCG strains in the intravesical treatment of non-muscle invasive urothelial carcinoma of urinary bladder-A real-world practice. Issue 9 (23rd September 2022) - Chen, Yu-Kuang; Huang, Eric Yi-Hsiu; Chang, Yen-Hwa; Kuo, Junne-Yih; Chung, Hsiao-Jen; Wu, Howard Hung-Hao; Lin, Tzu-Ping; Lin, Chih-Chieh; Fan, Yu-Hua; Huang, I-Shen; Lin, Alex T.L.; Huang, William J.
Abstract : Background: Bacillus Calmette–Guérin (BCG) has been well recognized as the first-line intravesical therapy for high-risk non-muscle-invasive bladder cancer (NMIBC). Oncotice, the Tice strain of BCG, serves as a viable alternative to the Connaught strain owing to the worldwide shortage of the latter. We retrospectively compared these two strains in terms of efficacy and adverse effects (AE) in patients who underwent at least one maintenance course after induction. Methods: In this single-institution, retrospective study, patients diagnosed with NMIBC who were administered either Connaught or Tice intravesical therapy were enrolled. Recurrence was defined as the reappearance of urothelial carcinoma. Progression was defined as stage/grade advance, metastasis, or cancer-related death. The primary outcomes were recurrence-free survival (RFS) and progression-free survival (PFS), and the secondary outcome was AE. Results: A total of 76 and 84 patients receiving Tice and Connaught, respectively were enrolled. The median follow-up periods for the Tice and Connaught groups were 32.0 months (range, 7-69 months) and 81.5 months (range, 9-154 months), respectively. Kaplan–Meier method showed no intergroup difference with regard to 3-year RFS and PFS. On Cox multivariate regression analysis, Tice was a significant predictor for inferior PFS (HR = 5.30; 95% CI, 1.11-25.29; p = 0.036). The AE incidence was 38.3% in the Connaught group and 25.0% in the Tice group ( p = 0.079). Conclusion: Tice and Connaught were comparable in terms of RFS, PFS, and AE for patients with NMIBC accepting BCG induction and at least one maintenance course in our real-world practice. However, Tice was a predictor of inferior PFS on multivariate analysis.